Potency Analysis of Mesenchymal Stromal Cells Using a Combinatorial Assay Matrix Approach - Chinnadurai, Raghavan; Rajan, Devi; Qayed, Muna; Arafat, Dalia; Garcia, Marco; Liu, Yifei; Kugathasan, Subra; Anderson, Larry J.; Gibson, Greg; Galipeau, Jacques (Cell reports (Cambridge), 2018)
Assays that can characterize MSC immune potency need to be identified for use in advanced clinical trials. MSCs possess a number of putative regenerative and immunomodulatory properties, and an assay matrix approach may best capture involved effector pathways. We have tested two assay systems to measure the potency of MSCs derived from human subjects: MSC secretome analysis and a quantitative RNA-based array for genes specific to immunomodulatory and homing properties of MSCs. Secretome analysis identified a unique cytokine signature that is upregulated by MSCs or downregulated in responder PBMCs and correlated with T cell suppression. Use of interferon-γ as a surrogate for the action of activated PBMCs on MSCs served as an alternative for the use of human PBMCs as responder cells in a potency assay. Our approach and results define and simplify the multifunctional or matrix responses of MSCs and may serve as a platform for robust potency analysis. [Display omitted] •T cell suppression by MSCs correlates with cytokine and morphogen expression•MSC and responder PBMC interactions are bidirectional•MSC potency affects the secretome and correlates with T cell suppression•The matrix response of MSCs to PBMCs is replicated by IFNγ stimulation Assays that inform on mesenchymal stromal cell (MSC) immune potency need to be defined in advanced clinical trials. Chinnadurai et al. tested an in vitro assay matrix approach combining molecular genetic and secretome analysis, elements of which could be deployed to define MSC immune modulatory potency.